Alfieri and "language books" (Prassi Ecdotiche della Modernità Letteraria, 2018)
The paper focuses on annotations jotted down by Vittorio Alfieri in the margins and endpapers of books related to language issues. A chronological path is sketched, from annotations dating from the first years of Alfieri’s « conversion » to literature, to annotations dating from is maturity. Special attention is paid to annotations dating from 1778-1779, where Alfieri carried on intensive studies of Italian language. Four type of annotation are described: lexical annotations; rationalisation of grammars and theorical texts; grammatical observations and ‘petulant’ annotations. Alfieri kept studying Italian language throughout his life: but the way he annotated books concerning language issues gradually changed over the time, as he achieved language proficiency.
Keywords: Vittorio Alfieri; notes; annotations; posts; linguistics; italian language